Formation of readiness of future teachers of physical culture for professional self-development during extracurricular work - Перевєрзєва, Світлана Василівна; Марчик, Валентина Іванівна (Pedagogy of Higher and Secondary Education, 2017)
In the article the issues of the use of effective forms of extracurricular physical training of future teachers with the formation of readiness for professional self-development have been considered. The authors have summarised and systemated data of scientific sources on the definition of students’ professional self-development consciousness. The process of preparation of future teachers of physical culture implies the formation of stable mental characteristics of an individual and it depends on the willingness of fulfillment of their abilities. Described forms and teaching methods make it possible to succeed in the educational process at the university, in personally oriented training and education of awareness of the value of physical culture and sports in extracurricular time. Characterized extracurricular work means the formation of readiness of future teachers of physical training for professional self-improvement in higher education; professional and social ones; competitive professional training; assistance in the formation of special competence-mastering the subject, critical understanding of theory and practice, demonstration of originality and creativity The issues of forming positive attitude of students to extracurricular vocational guidance have been identified, and the ways of positive influence, besides creating conditions to attract future teachers of physical training on a voluntary basis to the planning, organization and implementation of mass sports in high schools in extracurricular time have been defined. Mentioned above pedagogical conditions, functions and extracurricular forms of teachers of Physical Education, as a result of the experience cquired professional activity focuse on successful self-development of future teachers of physical culture and directly serve as a training professional direction.).